A new species of parasitoid wasp of the genus Encarsia (Hymenoptera: Aphelinidae) from Tamaulipas, Mexico - Myartseva, Svetlana N. (Instituto de Ecología, A.C., 2001)
Encarsia pinella sp. nov., reared from the diaspine scale Melanaspis sp. on Pinus spp. in the Reserve "El Cielo", Tamaulipas, México, is described. Keys to two taxonomic groups of species of the genus Encarsia (females) and six species of scales parasitoids in Mexico are given.